Micromixing and Co-Precipitation in Continuous Microreactors with Swirled Flows and Microreactors with Impinging Swirled Flows - Rufat Sh. Abiev; Yulia S. Kudryashova; Andrey V. Zdravkov; Nadezhda Yu. Fedorenko (Inorganics, 2023)
One of the promising methods for process intensification for micromixing, co-precipitation, and crystallization in continuous reactors is the use of vigorous vortices. A combination of the high intensity of the kinetic energy input with the small volume of the micromixing volume allows to concentrate the energy dissipation rate up to 104 W/kg and more. As the embodiment of such an idea, four new types of microreactors with intensively swirled flows were created and studied as a tool for continuous co-precipitation and crystallization. A correlation between residence time and segregation index was found: the smaller residence time, the higher energy dissipation rate and better quality of micromixing. A method for the synthesis of oxides of a number of transition metals in microreactors with intensively swirled flows with subsequent thermal treatment of co-precipitation products has been developed. This method was used to obtain ensembles of nanosized particles of zirconium oxides, as well as calcium and strontium fluorides. In comparison with the currently widely used hydro- and solvothermal methods, the proposed method has high productivity (around 10 m3/day for lab scale device), can significantly reduce the duration of the process, provides low energy consumption, does not require a large number of labor-intensive operations, is technologically advanced and easily scalable.